2004
DOI: 10.1002/jsfa.1797
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genotype and protein content on the baking quality of hearth bread

Abstract: The relationships between protein content and quality and the loaf characteristics of hearth breads made from the respective flours were investigated for 20 wheat genotypes, comprising both commercially grown cultivars and advanced breeding lines, grown in 1997 and 1998. In both years the average protein content was increased by increasing the level of nitrogenous fertiliser application, this effect being more pronounced in 1997 than in 1998. Grain samples were milled and evaluated for endosperm hardness, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
4
15
2
Order By: Relevance
“…Among the rheological properties studied, W was positive correlated to the HW ratio of loaves whereas the DDT showed a good but negative correlation to it. Concerning the DDT, these results were opposite to those obtained by Uhlen et al (2004) that found a high but positive correlation of this index to both the volume (R ¼ 0.89) and HW ratio of the loaf (R ¼ 0.90) of hearth bread. Nevertheless, Uhlen et al (2004) used a baking system different from that applied in the present research and this thing could explain the different results obtained by the two groups of researchers.…”
Section: Bread Quality Of Control and Supplemented Doughscontrasting
confidence: 99%
See 1 more Smart Citation
“…Among the rheological properties studied, W was positive correlated to the HW ratio of loaves whereas the DDT showed a good but negative correlation to it. Concerning the DDT, these results were opposite to those obtained by Uhlen et al (2004) that found a high but positive correlation of this index to both the volume (R ¼ 0.89) and HW ratio of the loaf (R ¼ 0.90) of hearth bread. Nevertheless, Uhlen et al (2004) used a baking system different from that applied in the present research and this thing could explain the different results obtained by the two groups of researchers.…”
Section: Bread Quality Of Control and Supplemented Doughscontrasting
confidence: 99%
“…Concerning the DDT, these results were opposite to those obtained by Uhlen et al (2004) that found a high but positive correlation of this index to both the volume (R ¼ 0.89) and HW ratio of the loaf (R ¼ 0.90) of hearth bread. Nevertheless, Uhlen et al (2004) used a baking system different from that applied in the present research and this thing could explain the different results obtained by the two groups of researchers. On the basis of correlation coefficient, probability level and standard error, the best single predictor of the SV was represented by the alveograph parameter W whereas the HW ratio was better predicted by the DDT.…”
Section: Bread Quality Of Control and Supplemented Doughscontrasting
confidence: 99%
“…The temperature during grain filling is among the environmental factors found to affect gluten quality. In Scandinavia, weaker gluten quality is reported in the seasons having cooler and wetter weather (Johansson and Svensson, 1998;Moldestad et al, 2011;Uhlen et al, 2004). Moldestad et al (2011) found the temperature during grain filling to be the weather parameter that was most strongly associated with gluten quality, and reported lower resistance to stretching of the gluten dough when the mean daily temperature drops below 17e18 C. Several researchers have performed experiments in controlled climate chambers and analysed gluten quality and composition (Johansson et al, 2005;Malik et al, 2013Malik et al, , 2011Randall and Moss, 1990;Uhlen et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…It is distributed through all parts of the grain but mostly concentrated in the endosperm (72.5% of the total protein) and aleurone layer (15.5% of the total protein). Although the protein content depends mainly on the environment and N fertilisation (Uhlen et al, 2004) the specific composition of the proteins of the endosperm is genetically determined (Wrigley et al 1982;Carrillo et al 1988).…”
Section: Proteinmentioning
confidence: 99%
“…Longstaff and McNab, (1986) found a significant difference in the starch content of two wheat varieties (Norman and Armada) when grown in the North or the South-East of the United Kingdom, with the starch content being higher in those grown in the South-East compared to the Northern areas. Variability in the CP content of wheat samples has also been correlated with nitrogen application on the growing wheat crops (Uhlen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%